2020
DOI: 10.1039/d0ra00430h
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced Raman spectroscopic studies on the adsorption behaviour of nitric oxide on a Ru covered Au nanoparticle film

Abstract: A SERS borrowing strategy with well-designed substrates has been developed to monitor the adsorption and dissociation of NO at Au/Ru surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The FT-IR peak located at 1436 cm –1 was assigned to the breathing mode of C–C bonds in a heterocyclic ring with strong intensities . Furthermore, the Raman and SERS spectra (Figure e) showed two similar peaks at 1447 and 1438 cm –1 , which were attributed to the breathing vibration of C–C bonds in the heterocyclic ring with different intensities. , However, the intensities of the SERS signals, in an absolute sense, would be difficult to use as a quantitative measurement of adsorption strength and adsorption capacity before careful calibration. The evolution of these signals in the current experiment can be a qualitative indicator for the adsorption strength between cations and the Ag(111) surface (Figure S15) when compared to an internal standard .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The FT-IR peak located at 1436 cm –1 was assigned to the breathing mode of C–C bonds in a heterocyclic ring with strong intensities . Furthermore, the Raman and SERS spectra (Figure e) showed two similar peaks at 1447 and 1438 cm –1 , which were attributed to the breathing vibration of C–C bonds in the heterocyclic ring with different intensities. , However, the intensities of the SERS signals, in an absolute sense, would be difficult to use as a quantitative measurement of adsorption strength and adsorption capacity before careful calibration. The evolution of these signals in the current experiment can be a qualitative indicator for the adsorption strength between cations and the Ag(111) surface (Figure S15) when compared to an internal standard .…”
Section: Resultsmentioning
confidence: 99%
“…To better study the role that cations played in reversible metal Ag electrodeposition, we have analyzed the adsorption behavior (Figure b,c) of different cations on the surface of the silver electrode. ,,, The adsorption of ions on the Ag surfaces could be accurately monitored via Raman and SERS techniques. Here, the adsorption of cations to the metal Ag nanoparticle film was monitored through the combination of FT-IR, Raman, and SERS spectra, as illustrated in Figure d,e. In the FT-IR spectra of DBPz-Br (Figure e), the band at 1281 cm –1 was attributed to the stretching vibration of the N-N.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction was repeated with Au@SiO 2 SHINs without Rh catalysts (Figure S2). Immediately after flowing NO (50 mL min −1 ), a band at ∼241 cm −1 was present, [32] which blue‐shifted to ∼265 cm −1 after 10 min (Figure S2a), likely related to molecular NO adsorption on Au (Au‐NO). Rhodin and co‐workers [40] found that CO dissociation adsorbed on a metal surface varies with the position of substrate in the periodic table and the same conclusions were made for NO, [38] which was further confirmed by Bond [41] .…”
Section: Resultsmentioning
confidence: 99%